Comparative Analysis of Performance of Hydro-mechanical Steering System and Ideal Steering System of the SPT trailer. (2017) - Ahmed, Shaikh Naveed; Darade, P.D.; Jagtap, K.R.; Ranjan, R.
Abstract: This paper presents the comparative analysis of the steering performance of two different steering mechanisms of an articulated semi-trailer. The vehicle under study is a 50 ton special purpose trailer (50T-SPT) used to carry heavy payloads. Characterization of the steering system of this vehicle has been carried out using multi body dynamics software called MSC ADAMS, by identifying the current steering ratios as a function of articulation angle between tractor and trailer. Mathematical formulation based on the Ackerman principle of steering is done to estimate the steering behavior and a comparative study was carried out. Both the path profile generated using the values of the steering angles obtained from the actual vehicle model and ideal steering model, were illustrated using AUTOTURN software.